The differences between the definitions of trapezoid in mathematics textbooks in Brazil - Mello , Elisabete Marcon (Seven Editora, 2023)
In geometry books and mathematics textbooks, two types of definition for trapezoids are found, one in which parallelograms are considered trapezoids and another in which they are not, therefore, these configurations determine two different hierarchical classifications for quadrilaterals. Which of these definitions is used most frequently in Brazilian mathematics textbooks? What problems can be caused by this duplicity of definition types? These questions drove the realization of this research, which consists of an analysis of mathematics textbooks for the 6th year of Elementary School. Of the twenty-five titles analyzed, most have definitions that do not consider parallelograms as trapezoids. It was possible to observe that each book presents the definition of trapezoid as if it were unique, which can create an obstacle for the student’s learning. A joint study between mathematicians and mathematics educators is considered important to deepen the theme and analyze the cognitive cost of maintaining different definitions for trapezoids in geometry. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-108